РЕСУРС МЕЖНАЦИОНАЛЬНОГО СОГЛАСИЯ И БАЛАНС НЕТЕРПИМОСТИ В СОВРЕМЕННОМ РОССИЙСКОМ ОБЩЕСТВЕ - Дробижева, Леокадия (Федеральное государственное автономное образовательное учреждение высшего профессионального образования «Национальный исследовательский университет «Высшая школа экономики», 2012)
Культурная сложность становилась вызовом для полиэтнических обществ даже в давно устоявшихся демократиях. Об этом говорят дискуссии о мультикультурализме, убийства на этнической почве в США и Европе, сожженные машины и этнополитические темы на выборах во Франции, Австрии, Германии. В России, казалось бы, этнокультурная сложность не увеличилась. В СССР русские составляли 51% населения, теперь по Всероссийской переписи 2010 г. русских в России 80,9% (в 2002 г. 80,64%); и список народов, насчитывающих более миллиона человек, не увеличился. Но дело в том, что этносоциальные и политические проблемы появляются не только из-за «бунта» этнических меньшинств, но и из-за самочувствия большинств. В статье мы постараемся показать ресурс тех установок в общественном сознании, идеологем и законодательных норм, которые могут обеспечивать межнациональное согласие в российском обществе и баланс нетерпимости негативных установок, идей и этнополитики, которые способны провоцировать межнациональную враждебность. В статье показано, как этот баланс меняется в связи с общим социально-политическим климатом в стране. Основным источником для анализа являются результаты общероссийского социологического исследования «20 лет реформ глазами россиян», проведенного Институтом социологии РАН в апреле 2011 г., данные социологических исследований в республиках Российской Федерации (Башкортостане, Татарстане и Саха (Якутии)), проведенные по сопоставимой программе в 2011-2012 гг. и материалы Европейского социологического исследования 2008 и 2010 годов. The resource of interethnic tolerance in the Russian multiethnic society as well as the balance of intolerance and exceptions is being analyzed in the article. The source of the analysis is based on the results of sociological survey '20 Years of Reforms as viewed by the Russians', which was conducted in 2011 by the Institute of Sociology at the Russian Academy of Sciences on a cross-regional sample with a total of 1750 respondents. The results of the research show that the balance of consent and intolerance in Russia depends on the activities of Russians in various fields such as institutions (family, school, higher education, mass-media), ideologies (construction of country images, heroes, positive norms of interaction, historical memory wars, formation of radical ethnic or civic nationalism, etc.), state policy (integration or assimilation, Russia as mutual home or the Russian state). The article defines problem zones and offers operational steps based on the necessity of avoiding the risks of splitting the society at the ethnical level. The author does not waive such terms as 'the political nation', 'the Russian identity' because they unite citizens independently of their nationality. She demonstrates that the Russian (civil) identity complies with the ethnic identity. As to the Russians as a nation, their strong connection with the state-civil identity is even more expressed than the one with the ethnic identity. At the same time a share of people with actualized ethnic identity is no less than that of among the Bashkirs, Tartars or Yakuts. Under these conditions mutual understanding and tolerance may vary. In discussion the author demonstrates the illegal character of now popular proposals to forbid the term 'state-base nation' as the state is formed by citizens, not by nationalities. It looks also illogical to limit the interests and demands of Russian people and other nationalities to the cultural aspects only, since their interests are wider including labor equality, access to the resources and participation in decision-making processes